Introducing hyaloid-sparing double capture: a novel technique in cataract surgery—anticipated clinical trial rationale and invitation - Arbisser, Lisa Brothers (Frontiers in Ophthalmology, 2026)
The state of the art of in-the-bag cataract surgery, though one of the most successful surgeries in ophthalmology, has significant room for improvement as a one-time, lifetime solution for optical clarity. Though optic capture techniques have been known since the 1990’s they are underutilized and not adequately explored or understood. This perspective not only explains their history and value but also clarifies the anatomy and suggests a proven improvement and a proposed study for another solution: hyaloid sparing double capture, to once again elevate the outcomes and lessen the complications of our routine surgery. Open your mind: hone your skills with this knowledge and help us move forward.